THE MANAGEMENT OF THE PROJECT-BASED LEARNING (PJBL) MODEL IN ENHANCING STUDENTS’ RELIGIOUS CHARACTER AT SMA NEGERI 1 CIRACAP AND SMA NEGERI 1 SURADE - Athori, Feri Firmansyah; Basnang Said (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
At SMA Negeri 1 Ciracap and SMA Negeri 1 Surade in Sukabumi Regency, West Java, the administration of Project-Based Learning (PjBL) is essential to developing students' religious character. The purpose of this study is to outline the ways in which PjBL management aids in the formation of religious character in these two high schools. Data were gathered through in-depth interviews, documentation, and observations involving Islamic Religious Education instructors, principals, and students using a qualitative descriptive case study methodology. The findings show that educators incorporate religious ideas into project planning, including digital dakwah materials and social religious activities. Teachers serve as facilitators during implementation, promoting moral responsibility, teamwork, and connections between projects and religious principles. Assessment is a comprehensive process that includes learning procedures, project goals, and changes in students' religious behavior. In order to foster a religious and participative learning culture, the management method emphasizes efficient collaboration between educators, students, and school officials. In accordance with the Pancasila Student Profile, this study concludes that well-managed PjBL is a creative way to enhance students' religious character and offers insightful information to Islamic Religious Education instructors and school policymakers on how to create curricula that foster moral and spiritual development in addition to academic success.